The management of Bochdalek congenital diaphragmatic hernia: a single center experience and review of the literature - Okay, Sefer Tolga; Sancar, Serpil; Özçakır, Esra; Güney Varal, İpek; Doğan, Pelin; Kaya, Mete (The European Research Journal, 2020)
Objectives: Congenital diaphragmatic hernia (CDH) is a rare congenital anomaly of the diaphragm with pulmonary hypoplasia and persistent pulmonary hypertension and has serious consequences. Despite recent diagnosis and treatment strategies, CDH is still a challenging condition. We aim to present our clinical experiences of CDH, and review of the literature.Methods: Data of CDH patients who were operated in our clinic between January 2010 and September 2018 were obtained from the patient's chart. The clinical course and results of the patients with Bochdalek type CDH were reviewed.Results: We performed diaphragmatic closure in 16 patients with Bochdalek CDH during study period. Fourteen (82%) cases were diagnosed antenatally. In 5 (29%) patients, preoperative pulmonary hypertension developed and nitric oxide was administered. Twelve of the sixteen patients (75%) underwent primary repair and 4 of them underwent prosthetic patch. Three patients were repaired thoracoscopically. Five (31%) patients died due to severe persistent pulmonary hypertension on postoperative period. There was no recurrence in our patients who were followed-up for a mean of 27 months. Conclusion: In the management of Bochdalek CDH, the clinical success has been increasing in parallel with the important developments with the application of new treatment modalities in the neonatal intensive care units and new surgical techniques in recent years.